REFLEKSI ATAS TUBUH DALAM KARYA PUTU SUTAWIJAYA “ENERGI TUNGGAL” - Pamungkas, Didung Putra; Y., Eva (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2023)
"Analyzing Putu Sutawijaya's painting titled "Energi Tunggal" (Single Energy) portrays the body as a central focus, through documentation and direct observation of his paintings, which are then analyzed using Roland Barthes' semiotic approach, Foucault's genealogy of the body, Ponty's Phenomenology, Heidegger's Existentialism, and Freud's Psychoanalysis. Roland Barthes' semiotic approach divides signs into denotation and connotation. At the denotative level, Putu depicts a figure's movement with the burdens surrounding it. At the connotative level, it explains that the burden on the social and value systems binds and does not liberate its people. Then Foucault describes the body as a soft body. Putu shows the absence of freedom that a free person owns over his own body. In Ponty's Phenomenology, the world is available to individuals. Thus, the relationship between humans and their world is never genuinely distant but needs to be more dialectical. Heidegger's Existentialism views the relationship of the body with its world. In his paintings, Putu sees that culture always constructs an individual, showing the form of a person's relationship with his world. Freud's Psychoanalysis on libido, there is a form of individual freedom to actualize themselves that is always limited by rules, values, and norms. Putu's work depicts efforts to break free but are still burdened by social considerations. This study on the painting is to spur the spirit of creating art and enrich new discourses in the Indonesian visual arts world.